2017
DOI: 10.1038/s41598-017-17560-2
|View full text |Cite
|
Sign up to set email alerts
|

Alternate partial root-zone drip irrigation improves water– and nitrogen– use efficiencies of sweet-waxy maize with nitrogen fertigation

Abstract: Alternate partial root–zone drip irrigation (ADI) or fertigation has favorable effect on crop water- and nitrogen- use efficiencies (WUE and NUE). However, the advantage of combined application of ADI and nitrogen fertigation on crop WUE and NUE remains unclear. A pot experiment was conducted to investigate the impact of three irrigation methods (CDI conventional drip irrigation (both halves of pot irrigated), ADI (both halves of pot alternatively irrigated) and FDI fixed partial root–zone drip irrigation (fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Shoot glutamine synthetase activity and NUtE shared most of the genotypic variation and contributed to PC2, which was mainly associated with cotton genotypes (Figures 5 and 6). Moreover, NUtE was negatively correlated with increasing nitrogen supply, which is in line with the previous results [70][71][72]. The reduction in NUtE with increasing nitrogen supply might be due to excessive storage of external N beyond plant requirements, and thus the external N cannot stimulate further growth [73].…”
Section: Variations In Morphophysiological and Biochemical Traits Aresupporting
confidence: 90%
“…Shoot glutamine synthetase activity and NUtE shared most of the genotypic variation and contributed to PC2, which was mainly associated with cotton genotypes (Figures 5 and 6). Moreover, NUtE was negatively correlated with increasing nitrogen supply, which is in line with the previous results [70][71][72]. The reduction in NUtE with increasing nitrogen supply might be due to excessive storage of external N beyond plant requirements, and thus the external N cannot stimulate further growth [73].…”
Section: Variations In Morphophysiological and Biochemical Traits Aresupporting
confidence: 90%
“…need to improve irrigation management in order to increase water use efficiency. Partial root-zone irrigation (PRI) is a water-saving irrigation technique that improves water use efficiency without reducing yield (Kang et al, 1997;Kang and Zhang, 2004;Fu et al, 2017). Previous reports showed that PRI is associated with a relatively high level of photosynthetic activity despite the reduced irrigation and decreased transpiration compared with conventional irrigation (Kirda et al, 2004;Zegbe et al, 2004;Tang et al, 2005).…”
mentioning
confidence: 99%
“…In addition, N translocation efficiency was defined as the N translocation amount divided by N uptake at silking. The NUE was calculated as the ratio of yield relative to N uptake amount of the whole plant at maturity (Fu et al, 2017).…”
Section: Grain Weight Yield and Nuementioning
confidence: 99%